Inside the Large Congregation - Beaumont, Susan (Rowman & Littlefield Publishers, 2011)
For five years, Alban Institute senior consultant Susan Beaumont has been giving voice to the organizational and leadership demands of large congregations. Through her work, she has identified five basic leadership systems that need to stay in alignment for the large church to function well for its size: clergy leadership roles, staff team design and function, governance and board function, acculturation and the role of laity, and forming and executing strategy. She has also learned that these five systems operate with some important but subtle distinctions in what Beaumont calls the professional church (400-800 in worship attendance), the strategic church (800-1,200), and the matrix church (1,200-2,000). Often, she has discovered, problems in a large congregation are related to the fact that one or more of the five systems is inappropriately structured for the size of the congregation. In other words, the church isn't acting its size. Beaumont is invested in helping large congregations 'rightsize' their leadership systems to better serve their ministry context. This book articulates why size matters and how it matters in the world of large congregations. It is written for anyone who wants to better understand the leadership and organizational dynamics of the large church anyone seeking to understand the challenges of leading from inside the large congregation.